The Appropriate Bargaining Unit: The Need for Policy Consistency by Canadian Labour Boards - McPhillips, David (Relations industrielles / Industrial Relations, 1988)
This paper discusses the policies of the Boards with regard to administrative changes, consolidations, accretions, mergers, partial raids and partial decertifications.